Determination of pore types in coquinas carbonates and their effects on formation factors and porosity exponents. Issue 1 (2nd January 2021) - Wang, Haitao
ABSTRACT: Calculation of the saturation of carbonates with various pore types and complicated pore structures in electrical resistivity models requires data on pore types and their effects on electrical resistivity. Therefore, the objectives are to determine the pore types and to investigate their effects on electrical resistivity. The pore types of three coquinas samples were determined by the distributions of experimental porosities and porosity exponents in the cross-plot of the dual porosity model and pore visualization from X-ray computerized tomography. A process-based method was applied to reconstruct the pore-scale models with different pore types. Their pore networks and electrical resistivity were extracted and calculated by the maximal ball and finite element methods, respectively. Fracture reduced the formation factor and porosity exponent. Connected vug increased the pore space that swept by the electrical current to reduce the formation factor while increasing the porosity exponent. Isolated vug undermined the pore space to increase the formation factor and porosity exponent. The effects of the tiny vug were much more obvious than the effects of the large one. This investigation will help to classify the pore types and propose electrical resistivity models that correspond to specific pore types and vug sizes in carbonate reservoirs.